The direct and indirect effect on online purchase decision through consumer satisfaction - Agus Nakkok Simanjuntak; Leonardo Davidsi Sipayung; Sri Ida Royani Simanjuntak; Orlando Steven; Lasma Lenida Rosinta Sianipar (Jurnal Mantik, 2023)
This study aims to analyze the effect of product quality, promotion, digital marketing and e-wom as independent variables on online purchasing decisions as the dependent variable through consumer satisfaction as a mediating variable. The test analysis model uses the outer model, inner model, direct effects, and specific indirect effects using the Smart PLS 4 application. Directly, the results of this study indicate that promotions, e-WOM, and consumer satisfaction have a positive and significant effect on online purchasing decision, while product quality and digital marketing have no significant effect on online purchasing decision. Digital marketing and e-wom have a positive and significant effect on consumer satisfaction, while product quality and promotions have no significant effect on customer satisfaction. Indirectly digital marketing and e-ewom have a positive and significant effect on online purchasing decision through consumer satisfaction. Meanwhile, product quality and promotion have no significant effect on online purchasing decision through consumer satisfaction.